A Review on Perceptions of the Teachers on the Applicability of Post-method Pedagogy in Language Teaching - Pokharel, Krishna (Lumbini Journal of Language and Literature, 2024)
This study aims to observe how the parameters of post-method pedagogy plays a role in English language teaching from the perspectives of teachers. To acknowledge these perspectives, this study reviewed 19 articles published in the relevant genres, particularly analyzing findings derived from these very writings. The research design employed in this study was qualitative and the methodology that I used was preferred reporting Items for systematic reviews and meta analysis. It elicits teachers’ inclination in the applicability and future scope of post-method pedagogy in English language classrooms. It reveals that many teachers have positive perspectives concerning the parameters of post method pedagogy and its strategies in teaching language; however, they have not succeeded for its complete application because of decade-long challenges existing in the classrooms. The result also discloses that the shift from transmission to transformative teaching techniques embraces a slow move. This study contributes to the practical understanding of the potentiality of three parameters in post-method pedagogy as a new paradigm to evaluate how current practices are ongoing in language teaching. Thus, traditional methods of teaching are constantly under inspection, and teachers’ struggle to transform their pedagogy in language teaching has a trivial impact on ongoing pedagogy.